THE IMPACT OF THE COVID-19 PANDEMIC ON MICRO AND SMALL SCALES BUSINESSES IN KOGI STATE, NIGERIA - Comfort Nwuchola; Sunday Zakeri; Dr.Akowe Joel; Dr. Haruna, Ruth Anyalewa; Omejeh, Timothy Enejoh (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Humans have witnessed three deadly pandemics so far in the twenty-first century which are associated with novel coronaviruses: SARS, Middle East respiratory syndrome (MERS), and COVID-19. All of these viruses, which are responsible for causing acute respiratory tract infections (ARTIs), are highly contagious and/or have caused high mortalities. Corona was treated as a simple non-fatal virus till 2002. Coronavirus causes respiratory infections including pneumonia, colds, sneezing, and coughing while in animals it causes diarrhea and upper respiratory diseases. Soon after the outbreak of the COVID-19 pandemic, many governments began extending financial and other forms of support to micro, small, and medium enterprises (MSMEs) and their workers because smaller firms are more vulnerable to negative shocks to their supply chain, labor supply, and final demand for goods and services than larger firms, and this was as a result of the containing modalities for curtailing the spread of this deadly disease. Since MSMEs are diverse, however, the severity of the pandemic’s impact on them varies considerably depending on their characteristics. This paper attempts to deepen our understanding of the impact of the pandemic on SMEs, especially their employment, sales revenue, and cash flow in Kogi State, Nigeria. Where the researchers are keen on identifying the coping strategies as well as the possibility of switching over as a survival measure in SMEs. One of the strategic implications of our study is the need to address social protection approaches such as palliative measures, tax waivers, and soft loans, which can help to cushion the effect Covid-19 has on Micro and Small Scales Businesses in Kogi State.